The 4G to 5G Network Architecture Evolution in Australia - Soldani, David; Shore, Malcolm; Mitchell, Jeremy; Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2018)
This paper provides a review of selected design and security aspects of 5G systems and addresses key questions about the deployment scenarios of Next Generation Radio Access Networks in Australia. The paper first presents the most relevant 5G use cases for the Australian market in 2018-19, and beyond; 5G concept and definitions; 3GPP updates, in terms of system architecture and enabling technologies and corresponding timelines; and spectrum availability, linked to possible 5G deployments in Australia. Then, the paper discusses the 5G functional architecture, possible configuration options, enabling technologies and network migration strategies and related 5G security, in Australia and globally. This is followed by a description of the possible 5G deployment scenarios in a multivendor environment and includes, as a case study, the Huawei product portfolio and site solution in Australia. The paper concludes with a discussion on the potential benefits of a telecommunications security assurance centre to improve the whole-of-life security assurance of critical telecommunications infrastructure and why it is important for the Australia telecommunications sector.